Development and implementation of Phleos, a web-based tool for the data collection on Hypereosinophilic syndrome: the Italian Network on HES (INHES) study protocol - Nicola, Stefania; Caminati, Marco; Borrelli, Richard; Lo Sardo, Luca; Corradi, Federica; Badiu, Iuliana; Vacca, Angelo; Carlucci, Palma; De Paulis, Amato; Mormile, Ilaria; Zurlo, Marco; Di Gioacchino, Mario; et al. (Frontiers in Immunology, 2025)
Hypereosinophilic syndrome (HES) is a heterogeneous group of disorders characterised by persistent hypereosinophilia associated with organ damage. Due to its rarity and heterogeneity in its clinical presentation, HES remains underdiagnosed or misdiagnosed, often leading to delayed diagnosis and irreversible organ damage. The complexity of HES diagnosis is even more complicated due to the absence of standardised criteria. Moreover, the lack of structured referral pathways among specialists, including allergists, clinical immunologists, haematologists, and rheumatologists, further hinders optimal patient care. To address these challenges, the Italian National Hypereosinophilic Syndrome (INHES) Network aimed to enhance the diagnosis, management, and research of HES. INHES objectives also include connecting specialised centres, facilitating data collection on HES and eosinophilic-associated conditions, and improving healthcare standards through consensus guidelines. To do this, INHES has created a web-based platform called “Phleos” to develop a comprehensive referral map, ensuring timely and appropriate patient access to expert care. Phleos is a web-based datasheet, per GDPR regulations, to systematically collect anonymised clinical data, including absolute eosinophil counts, organ involvement, laboratory parameters, instrumental assessments, and treatments. A structured classification system enables differentiation among idiopathic, lymphocytic, myeloid, familial, reactive, and overlap forms of HES. Moreover, the platform integrates standardised diagnostic pathways and treatment protocols to harmonise patient care across participating centres. The INHES Network aims to mitigate diagnostic delays, optimise therapeutic decision-making, and advance research in eosinophilic disorders by fostering interdisciplinary collaboration and establishing a unified framework. This initiative represents a crucial step toward a cohesive national strategy, ultimately improving clinical outcomes for HES patients in Italy.